Interactive simulated patient—an advanced tool for student-activated learning in medicine and healthcare - Bergin, Rolf A; Fors, Uno G.H (Computers and education, 2003)
An advanced learning system for interactive simulation of patient cases (ISP) is described. The system was designed to meet specific pedagogical needs where student activation and problem orientation were two of the key issues. The system includes features such as video based illness history-taking function using free text input, highly interactive physiological examination procedures, extensive laboratory tests and detailed user feedback. The system was constructed mainly in Authorware Professional, starting more than 10 years ago, and it is now available in refined versions in different languages. Twelve pedagogical and three technical features were initially defined for the project. All of these aims were fulfilled. The ISP system has been successfully used in education, and in international collaboration, including three applicability field tests. The system is also a powerful research tool for studying for instance medical decision-making.